Eyelid Malposition, the Basic Examination: Oral Presentation - Observational Study - Ophthalmologist - HENDRIATI JEFRIANTO (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Eyelid malposition is when the eyelids become abnormally positioned due to various causes. The disorder is not aesthetically-pleasing and can lead to visual and ocular problems, which can be serious. The main cause of eyelid malposition is aging, as the tissues surrounding the eyes relax as we age. It can also occur as a result of paralysis of the facial nerve (Bell's palsy), trauma, scarring, and surgery Methods : The types of eyelid malposition are: 1)Ptosis, a drooping upper eyelid, with difficulty in opening the eyelid voluntarily. In some cases, it is so severe that the eyelid covers the axis of the pupil and hinders correct vision in the affected eye. 2)Entropion, inward turning of the eyelid towards itself. It may be the lower eyelid or the upper eyelid, causing the eyelashes to rub against the cornea and eye surface, and 3)Ectropion, is the rotation towards the outside of the lower eyelid. Very often, it causes the tears to build up at the mid point without being able to drain and the patient notices their eye watering. Results : There are some examination for each type eyelid malpositions, like for ptosis: fissure palpebral vertical, fissure palpebral horizontal, levator function, margin limbal distance, margin reflex distance, and bell’s phenomenon. Examination for entropion and ectropion including squeeze test, distraction test, snap and snap-back test, medial and lateral canthal laxity. Conclusion : Careful examination is required to diagnose and manage eyelid malposition.